A green synthesis approach toward large-scale production of benzalacetone via Claisen–Schmidt condensation. Issue 45 (13th October 2022) - Sun, Ruolun; Han, Chenhui; Xu, Jingsan
Abstract : A stirring-induced emulsion system enables 99% selectivity to the mono-condensation product of a Claisen–Schmidt reaction. The system showed good cyclic performance and can be easily scaled up to kilogram-level for the production of benzalacetone. Abstract : Claisen–Schmidt (CS) condensation between acetone and benzaldehyde with NaOH as the catalyst is a well-recognized pathway for the synthesis of benzalacetone (BA). However, this process is compromised by a side reaction, i.e., a second CS reaction between benzaldehyde and the BA product. In this work, we designed a stirring-induced emulsion synthesis technique for the cyclic and scaling-up production of BA with 99 ± 1% selectivity, without the use of surfactants. In this approach, the water-soluble acetone and NaOH were separated from the oil-soluble benzaldehyde by the organic–aqueous phase interface, such that the CS condensation could only be executed at the liquid interface. The just-formed BA molecules diffuse to the interior of the oil solvent, where any subsequent CS post-reaction is rendered negligible, owing to the absence of NaOH. The oil phase containing the BA molecules can be easily separated from the aqueous solution by stopping stirring and undisturbed standing, allowing for a large-scale production protocol. As a proof of concept, over 1 kg of BA was produced in the laboratory with high yield and purity.